Singular Value and Matrix Norm Inequalities between Positive Semidefinite Matrices and Their Blocks - Feng Zhang; Rong Ma; Chunwen Zhang; Yuxin Cao (Journal of Mathematics, 2024)
In this paper, we obtain some inequalities involving positive semidefinite 2×2 block matrices and their blocks.